VALUE: EMPIRICS AND THEORY - Egorov, Dmitry; Dyatlov, Yuriy; Bogdanov, Maksim; Shushpanov, Evgeni; Egorova, Angela (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Disclosure of the essence of the category "value" is not a prerequisite for its use: the introduction of this concept is correct and simple a priori. At the same time, it is obviously desirable. Objectives: 1) to show the connection between the concept of "value" and the empirical level; 2)to justify the interpretation of value from the perspective of information theory. Results. Manifestations of the "value" category in economic practice: the notions of "fair price", "reasonable profit", statistics of input-output balances, the world practice of planning of long-term energy production projects, etc. An adequate interpretation of value is the information concept: at the basis of value as the result of labor, and the rarity of a thing is information. Value is an information measure of the object’s worth. The complexity of operationalization does not ensue the unscientific (metaphysical) character of the concept of "value" as such. From the recognition of value as an objective basis for the observable price phenomenon, there appear very specific consequences: 1) feedback through the market must have an objective basis as a starting measure, that is, money must have a standard; 2) in some cases direct pricing (and / or their directive definition) is justified and appropriate.